Physiological importance of Dincharya as preventive approach towards Indriya Vikara. - Jain, Rahul; Tanwar, Ankur Kumar; Singh, Priti; Bhojani, Meera K (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Indriyas are responsible for the Yathartha Anubhava or true unadulterated knowledge of everything around us. This knowledge will hamper when Nidana Sevana occurs and due to which Dushita Doshas (or imbalanced Doshas) reach the Adhisthana of Indriyas and leads to total (Upghata) or partial (Uptapa) loss of function of that Indriya. Ayurveda have various concept of healthy and happy life, Dincharya is one of such important concepts. Dincharya mentioned in Ayurvedic texts give the prophylaxis protocol for preventing this type of Indriya Vikara and maintaining the physiological functioning of Indriyas properly. Methods: Authentic text of Ayurveda, pubmed and other contemporary textbook referred for the collection of data related to Dincharya and Indriya(senses). Result: Acharyas mentioned that one should wake up in Brahma Muhurta because that increases the longevity and maintain Dhatu Samya Avastha of the body. Some practices in Dincharya gives Bala to Urdhavjatru (Adhisthan of all Indriyas) and prevent diseases of Urdhavjatru(eyes, nose, ear, head, mouth). These practices are Anjana, Dhoompaan, Nasya, Karnapooran, Gandoosh-Kaval Dhaaran, Dantadhaavan,Jihva Nirlekhan etc. Conclusion: Dincharya practices have a deep impact and numerous benefits for our Indriyas hence one should give them place in their daily routines.